MODERN DIAGNOSTICS AND TREATMENT METHODS OF JUMPING AND WRIST JOINT SYNOVITIS IN SPORT HORSES (Лучшие интеллектуальные исследования, 2025)
Abstract . This in the article on sports horses jump downloads as a result appearance to be wrist ( carpal ) joint synovitis , its clinical looks , modern diagnostics methods and effective treatment approaches illuminated . The disease early in stages to be determined and right​ therapy measures for sport horses functional activity in recovery important importance profession will reach .